Bioethics in the world’s constitutions - Varsi Rospigliosi, Enrique (Acta Bioethica, 2002)
The author analyses a compared Constitutional Law, identifying 37 fundamental laws that include bioethic principles in their norms, such as the respect for human dignity in everything related to scientific investigation, genetic identity's protection, the right to investigate paternity, recognition of future generation's rights, etc. A proposition to incorporate bioethic norms in the future Constitution was made by the Peruvian Congress. Several of the principles just mentioned, and others stated there, if approved in the Fundamental Chart, will turn Peru into the pioneer in constitutional regulation of the new topics related to life's sciences.